ANALYSIS OF THE IMPLEMENTATION OF THE CORE TAX ADMINISTRATION SYSTEM TO IMPROVE TAXPAYER COMPLIANCE (CASE STUDY AT KPP PRATAMA PARE KEDIRI) - Ersamawanti, Herfika; Agustin, Beby Hilda; Isnaniati, Siti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Core Tax Administration System sebagai sistem administrasi pajak yang merupakan bagian dari Core Tax Administration System is a tax administration system which is part of the government's efforts to carry out tax reform. The Core Tax Administration System can simplify the business process of implementing tax administration, both for the Directorate General of Taxes in carrying out their duties and for taxpayers in fulfilling their tax obligations. The Core Tax Administration System is a tax administration business process redesign project through the development of a COTS (Commercial Off-the-Shelf) based information system accompanied by improvements to the tax database. This research uses qualitative descriptive. The aim of this research is to find out the results of the analysis of the implementation of the core tax administration system to increase taxpayer compliance (study at KPP Pratama Pare Kediri). The data collection techniques used in this research are interviews, observation and documentation. The results of this research reveal that the main strength of KPP Pratama Pare Kediri lies in its strong commitment to implementing tax digitalization through the core tax administration system, accompanied by the ability to disseminate technology and relevant tax policies to taxpayers. However, the weaknesses faced include low taxpayer awareness and mastery of digital services, as well as KPP's internal challenges related to adaptation from conventional to digital systems and system integration that is not yet optimal. Great opportunities arise along with the increasingly widespread digitalization trend in society. This opens up space for KPP Pratama Pare Kediri to develop more modern and integrated tax services, as well as utilize social media for tax education and socialization. However, the threat of taxpayer behavior that is still not fully compliant and difficulties in digitally reporting annual tax returns remain challenges that must be faced.